PAHSAs enhance hepatic and systemic insulin sensitivity through direct and indirect mechanisms - Zhou, Peng (J Clin Invest, 2019)
Palmitic acid esters of hydroxy stearic acids (PAHSAs) are bioactive lipids with antiinflammatory and antidiabetic effects. PAHSAs reduce ambient glycemia and improve glucose tolerance and insulin sensitivity in insulin-resistant aged chow- and high-fat diet–fed (HFD-fed) mice. Here, we aimed to determine the mechanisms by which PAHSAs improve insulin sensitivity. Both acute and chronic PAHSA treatment enhanced the action of insulin to suppress endogenous glucose production (EGP) in chow- and HFD-fed mice. Moreover, chronic PAHSA treatment augmented insulin-stimulated glucose uptake in glycolytic muscle and heart in HFD-fed mice. The mechanisms by which PAHSAs enhanced hepatic insulin sensitivity included direct and indirect actions involving intertissue communication between adipose tissue and liver. PAHSAs inhibited lipolysis directly in WAT explants and enhanced the action of insulin to suppress lipolysis during the clamp in vivo. Preventing the reduction of free fatty acids during the clamp with Intralipid infusion reduced PAHSAs’ effects on EGP in HFD-fed mice but not in chow-fed mice. Direct hepatic actions of PAHSAs may also be important, as PAHSAs inhibited basal and glucagon-stimulated EGP directly in isolated hepatocytes through a cAMP-dependent pathway involving Gα(i) protein–coupled receptors. Thus, this study advances our understanding of PAHSA biology and the physiologic mechanisms by which PAHSAs exert beneficial metabolic effects.